2008
DOI: 10.1037/0893-3200.22.2.203
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of the death of a child on parents' adjustment in midlife.

Abstract: The death of a child is a traumatic event that can have long-term effects on the lives of parents. This study examined bereaved parents of deceased children (infancy to age 34) and comparison parents with similar backgrounds (n = 428 per group) identified in the Wisconsin Longitudinal Study. An average of 18.05 years following the death, when parents were age 53, bereaved parents reported more depressive symptoms, poorer well-being, and more health problems and were more likely to have experienced a depressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
248
1
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(275 citation statements)
references
References 38 publications
14
248
1
12
Order By: Relevance
“…For many people the distress triggered by loss does not dissipate within a few short months, but it can last for many years (Carnelley, Wortman, Bolger, & Burke, 2006;Rogers, Floyd, Seltzer, Greenberg, & Hong, 2008). Conversely, however, the assumption that the loss of a loved one inevitably produces high levels of enduring psychological distress also has been found to be incorrect, at least for a significant proportion of bereaved persons .…”
Section: Grief and Posttraumatic Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…For many people the distress triggered by loss does not dissipate within a few short months, but it can last for many years (Carnelley, Wortman, Bolger, & Burke, 2006;Rogers, Floyd, Seltzer, Greenberg, & Hong, 2008). Conversely, however, the assumption that the loss of a loved one inevitably produces high levels of enduring psychological distress also has been found to be incorrect, at least for a significant proportion of bereaved persons .…”
Section: Grief and Posttraumatic Growthmentioning
confidence: 99%
“…Religion/spirituality may serve as both a framework promoting growth through increased sense of meaning and purpose (Rogers et al, 2008), as well as a form of growth through deepening faith and conviction. Finding meaning in one's life following a loved one's death can represent a spiritual change that may result from bereavement (Balk, 1999).…”
Section: Grief and Posttraumatic Growthmentioning
confidence: 99%
“…Previous research has found that bereaved parents may experience mental health disorders such as depression, anxiety, insomnia, prolonged grief disorder (PGD), post-traumatic stress disorder (PTSD) and suicidal behaviours (Harper, O’Connor, & O’Carroll, 2014; Lannen, Wolfe, Prigerson, Onelov, & Kreicbergs, 2008; Rogers, Floyd, Seltzer, Greenberg, & Hong, 2008). The loss of a child is also associated with worse physical health problems in the long term (Lannen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The death of a child can lead to parents experiencing long-term negative psychological responses, such as increased depressive symptoms (Rogers, Floyd, Seltzer, & Hong, 2008), anxiety (Buchi et al, 2007), and complicated grief (Zetumer et al, 2015). Bereaved parents have also been found to experience relationship difficulties (Rogers et al, 2008) and poorer physical health (Li, Hansen, Bo Mortensen, & Olsen, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Bereaved parents have also been found to experience relationship difficulties (Rogers et al, 2008) and poorer physical health (Li, Hansen, Bo Mortensen, & Olsen, 2002). In a study of bereavement outcomes, Gamino, Sewell, and Easterling (2000) highlighted that one of the factors associated with increased experiences of grief was younger age of the deceased.…”
Section: Introductionmentioning
confidence: 99%